K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

10 tháng 10 2019

\(x^4+2\)

\(=x^4+2x^2+1-\left(2x^2-1\right)\)

\(=\left(x^2+1\right)^2-\sqrt{2x^2-1}^2\)

\(=\left(x^2+1-\sqrt{2x^2-1}\right)\left(x^2+1+\sqrt{2x^2-1}\right)\)

10 tháng 10 2019

\(x^4+2\)

\(=x^4+4x^2+2-4x^2\)

\(=\left(x^2+2\right)^2-4x^2\)

\(=\left(x^2+2-2x\right)\left(x^2+2+2x\right)\)

\(=\left(x-1\right)^2\left(x+1\right)^2\)

4 tháng 9 2021

x5-x4-30x3=x3(x2-x-30) = x3(x-6)(x+5) 

4 tháng 9 2021

\(x^5-x^4-30x^3=x^3\left(x^2-x-30\right)=x^3\left(x-6\right)\left(x+5\right)\)

NV
1 tháng 9 2021

\(=\left(x^6+2x^5+x^4\right)-2\left(x^5+2x^4+x^3\right)+2\left(x^4+2x^3+x^2\right)\)

\(=x^2\left(x^2+x\right)^2-2x\left(x^2+x\right)^2+2\left(x^2+x\right)^2\)

\(=\left(x^2+x\right)^2\left(x^2-2x+2\right)\)

\(=x^2\left(x+1\right)^2\left(x^2-2x+2\right)\)

1 tháng 9 2021

good teacher

\(x^4+6x^3+11x^2+6x+1\)

\(=x^4+3x^3+x^2+3x^3+9x^2+3x+x^2+3x+1\)

\(=\left(x^2+3x+1\right)^2\)

\(x^4+6x^3+7x^2-6x+1\)

\(=x^4-2x^2+1+6x^3+9x^2-6x\)

\(=\left(x^2-1\right)^2+6x\left(x^2-1\right)+9x^2\)

\(=\left(x^2+3x-1\right)^2\)

NV
1 tháng 9 2021

\(=\left(x^4+x^3+x^2\right)+\left(x^2+x+1\right)\)

\(=x^2\left(x^2+x+1\right)+\left(x^2+x+1\right)\)

\(=\left(x^2+1\right)\left(x^2+x+1\right)\)

\(x^4+x^3+2x^2+x+1\)

\(=x^4+x^3+x^2+x^2+x+1\)

\(=\left(x^2+x+1\right)\left(x^2+1\right)\)

4 tháng 9 2021

\(\left(x^2+6x-1\right)^2+2x^2+x^4+2\left(x^2+6x-1\right)\left(x^2+1\right)\)

\(\left(x^2+6x-1\right)^2+2\left(x^2+6x-1\right)\left(x^2+1\right)+\left(x^2+1\right)^2-1=\left(x^2+6x-1+x^2+1\right)^2-1=\left(2x^2+6x\right)^2-1=\left(2x^2+6x-1\right)\left(2x^2+6x+1\right)\)

\(\left(x^2+6x-1\right)^2+2\left(x^2+6x-1\right)\left(x^2+1\right)+x^4+2x^2\)

\(=\left(x^2+6x-1\right)\left(x^2+6x-1+2x^2+2\right)+x^4+2x^2\)

\(=\left(x^2+6x-1\right)\left(3x^2+6x+1\right)+x^4+2x^2\)

\(=\left(2x^2+6x-1\right)\left(2x^2+6x+1\right)\)

10 tháng 11 2021

=3x(x+2y)

10 tháng 11 2021

=3x(x+2y)

4 tháng 9 2021

\(2x^2+x-6\)

\(=2x^2-3x+4x-6\)

\(=x\left(2x-3\right)+2\left(2x-3\right)\)

\(=\left(2x-3\right)\left(x+2\right)\)

Tham Khảo

\(6x^2-13x+6\)

\(=6x^2-9x-4x+6\)

\(=\left(2x-3\right)\left(3x-2\right)\)

2 tháng 9 2021

x2-2x-15=(x2-5x)+(3x-15)=x(x-5)+3(x-5)=(x-5)(x+3)

2 tháng 9 2021

Bạn ghi lộn đề rồi bạn phải là 3x chứ ko phải là 2x.